2013
DOI: 10.26889/9781907555800
|View full text |Cite
|
Sign up to set email alerts
|

US Tight Oils

Abstract: The contents of this paper are the author's sole responsibility. They do not necessarily represent the views of the Oxford Institute for Energy Studies, of any of the Institute's members, and/or of the author's other affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…168 In another study, Yang also used a ruthenium catalyst, RuCl 3 , in the presence of hydriodic acid and hydrogen gas, to convert sugars (xylose, glucose, fructose) into tetrahydrofuran derivatives (2,5-dimethyltetrahydrofuran and 2-methyltetrahydrofuran), which can be used as biofuels. [170][171][172] In an indepth study of the mechanism, Yang and Grochowski found that both the acid (HI) and the catalyst (rhodium chloride) play important roles in the dehydration and hydrogenation of fructose. 173 Additional processes which yield biofuels from sugars and carbohydrates have been covered in a recent publication by Dutta et al 174 Heterogeneous processes.…”
Section: Reduction Of Sugars: Catalytic Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…168 In another study, Yang also used a ruthenium catalyst, RuCl 3 , in the presence of hydriodic acid and hydrogen gas, to convert sugars (xylose, glucose, fructose) into tetrahydrofuran derivatives (2,5-dimethyltetrahydrofuran and 2-methyltetrahydrofuran), which can be used as biofuels. [170][171][172] In an indepth study of the mechanism, Yang and Grochowski found that both the acid (HI) and the catalyst (rhodium chloride) play important roles in the dehydration and hydrogenation of fructose. 173 Additional processes which yield biofuels from sugars and carbohydrates have been covered in a recent publication by Dutta et al 174 Heterogeneous processes.…”
Section: Reduction Of Sugars: Catalytic Hydrogenationmentioning
confidence: 99%
“…Under mild temperature (<115 °C) and moderate hydrogen pressure (300 psi H 2 ), product yields of 61% and 41% were retained from inulin and corn stover, respectively. [170][171][172] Mineral acidsnon-catalytic conversion mediahave also very effectively been used to directly convert raw biomass into levulinic acid in commercialized processes. Researchers have had significant success as yields range between 50-80%.…”
Section: Chemical Crackingmentioning
confidence: 99%